2017
DOI: 10.1038/gim.2016.208
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of participants in the citizen science of microbiomics: data from the British Gut Project

Abstract: PurposeThe establishment of databases for research in human microbiomics is dependent on the recruitment of sufficient numbers and diversity of participants. Factors that support or impede participant recruitment in studies of this type have not yet been studied. MethodsWe report the results of a survey aimed at establishing the motivations of participants in the British Gut Project, a research project that relies on volunteers to provide samples and to help fund the project. ResultsThe two most frequently rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
14
2
Order By: Relevance
“…Our participant’s strongest motivations for taking part in the study were personal interest and a desire to contribute. Previous studies have also found these two reasons to be important to participants but, contrary to our study, tend to find that the desire to contribute is most common and personal interest is second [1618]. This may be because other studies have had a clearer link between participation and a specific research outcome such as finding a cure for a medical condition.…”
Section: Discussioncontrasting
confidence: 98%
“…Our participant’s strongest motivations for taking part in the study were personal interest and a desire to contribute. Previous studies have also found these two reasons to be important to participants but, contrary to our study, tend to find that the desire to contribute is most common and personal interest is second [1618]. This may be because other studies have had a clearer link between participation and a specific research outcome such as finding a cure for a medical condition.…”
Section: Discussioncontrasting
confidence: 98%
“…Different diver types have similar preferences and motivations to participate in CS, but there are important differences in their profile that could affect their participation in CS projects. For example, the differences in education level could influence their decision to participate, since a low level of education has been reported as a barrier to CS projects (Savio et al, 2017) and can affect data quality (Delaney et al, 2008). Our findings show that artisanal fishermen, despite their comparatively basic science literacy, have a high level of diving experience.…”
Section: The Diversity Of Divers and Designing Cs Projectsmentioning
confidence: 83%
“…Following suit, multiple nationwide and cohort-specific studies were conducted to understand the impact of the gut microbiome. 21 , 22 . These studies led to an exponential rise in available gut microbiome datasets across multiple cohorts.…”
Section: Background and Summarymentioning
confidence: 99%